Effektivitas Birthing Ball pada Ibu Primipara terhadap Persalinan Kala Dua - Setiana Andarwulan; Miftahul Hakiki (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2023)
Childbirth will cause feelings of anxiety for a mother who has never given birth at all. Labor can be passed comfortably through the provision of methods that can help speed up the delivery process. One of them is the birthing ball method. This research was conducted to find out the effect of birthing balls on the duration of the second period of labor at Mitra Sehat Mandiri Clinic in Sidoarjo. The research was conducted with an analytic design with a quasi-experimental method. The sample consisted of 32 primigravida pregnant women with a gestational age of 36 weeks, assigned to the intervention and control groups with inclusion and exclusion criteria determined by the researcher. Data analysis used the independent t statistical test. The results showed that there was effectiveness in using the birthing ball method for the duration of the second period of labor with a significance value of p = 0.000. Mothers who use the birthing ball technique will be better prepared for childbirth.